I will survive: Pricing strategies of financially distressed firms - Ioana A. Duca; José Manuel Montero; Marianna Riggi; Roberta Zizza (European Central Bank (ECB), 2018)
We consider a standard result of customer market theory: if firms have stable customer relations and face financial frictions, they may keep prices relatively high on their locked-in shoppers to maintain short-term profits at the expense of future market shares in times of low demand and vice versa in times of high demand. We extend this theoretical framework so that the countercyclical behaviour of price margins is strengthened by the expected persistence of demand and the procyclicality of competitive pressures. We test these predictions for Italian firms participating in the 2014 Wage Dynamics Network Survey. All things being equal, financially constrained firms charge higher markups when faced with low demand; this behaviour is more evident when demand is perceived as being persistent. Our findings suggest that the severity of financial constraints in Italy was one of the causes of the sustained growth of prices in 2010-2013.
Keywords: C25; C26; D22; L11; 330; markups; fiancial frictions; customer market